2019
DOI: 10.3758/s13414-019-01906-1
|View full text |Cite|
|
Sign up to set email alerts
|

Extra-foveal Processing of Object Semantics Guides Early Overt Attention During Visual Search

Abstract: Eye-tracking studies using arrays of objects have demonstrated that some high-level processing of object semantics can occur in extra-foveal vision, but its role on the allocation of early overt attention is still unclear. This eye-tracking visual search study contributes novel findings by examining the role of object-to-object semantic relatedness and visual saliency on search responses and eye-movement behaviour across arrays of increasing size (3, 5, 7). Our data show that a critical object was looked at ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 85 publications
(118 reference statements)
4
21
1
Order By: Relevance
“…This manipulation critically differs from Seckin et al, (2016), where distractors belonging to different semantic categories were presented together with semantically related distractors. We previously showed that in young adults, our manipulation led to a "semantic pop-out" effect whereby participants looked at a critical object earlier, and for longer, when it was semantically unrelated than related to the other distractors (Cimminella et al, 2020). This finding indicated that, in young adults, the rapid and complex extraction of object semantics occurs in extra-foveal vision, and it influences the early allocation of overt attention (see also Nuthmann et al, 2019;and Borges et al, 2020, for corroborating results in healthy older adults using naturalistic scenes).…”
Section: Preserved Extra-foveal Processing Of Object Semantics In Alzheimer's Diseasementioning
confidence: 92%
See 4 more Smart Citations
“…This manipulation critically differs from Seckin et al, (2016), where distractors belonging to different semantic categories were presented together with semantically related distractors. We previously showed that in young adults, our manipulation led to a "semantic pop-out" effect whereby participants looked at a critical object earlier, and for longer, when it was semantically unrelated than related to the other distractors (Cimminella et al, 2020). This finding indicated that, in young adults, the rapid and complex extraction of object semantics occurs in extra-foveal vision, and it influences the early allocation of overt attention (see also Nuthmann et al, 2019;and Borges et al, 2020, for corroborating results in healthy older adults using naturalistic scenes).…”
Section: Preserved Extra-foveal Processing Of Object Semantics In Alzheimer's Diseasementioning
confidence: 92%
“…Therefore, the aims of the present study were twofold: (1) to establish whether processing of semantic information about objects is preserved in AD and, if so, (2) to determine whether it can occur through extra-foveal vision, as shown in our previous work on healthy younger adults (Cimminella, et al 2020). We used the experimental paradigm we previously developed, reported in observed ceiling search performance on young adults in our previous study, but for older adults, a semantically related search object (e.g., a car) in target-absent trials may lead to greater memory demands, i.e., the object is not present in the context.…”
Section: Preserved Extra-foveal Processing Of Object Semantics In Alzheimer's Diseasementioning
confidence: 99%
See 3 more Smart Citations